"This Isn't About Casey Anthony Anymore": Political Rhetoric and Caylee's Law. (June 2016) - Socia, Kelly M.; Brown, Elizabeth K.
The 2011 trial of Casey Anthony for the murder of her child, Caylee, dominated media, public, and political attention in the United States. Anthony's acquittal prompted many lawmakers to rally around "Caylee's Law, " legislation that criminalizes the failure to report a missing child. This article considers the political rhetoric of Caylee's Law by qualitatively evaluating statements made by state policymakers across the United States for the 12 months following Anthony's acquittal. Policymakers' rhetoric on Caylee's Law exemplified the tendency to mobilize political action around "triggering events" through claims-making, to justify new penal legislation on the basis of worst case scenarios and public fears, and to demonize the accused in ways that reaffirm social solidarity in the face of heinous crimes. Policymakers used a variety of interconnected techniques to make claims about child protection, to justify the need for Caylee's Law, and to label and degrade Casey Anthony.